The increasing trend of childhood cancers in Sri Lanka: analysis of National Cancer Registry Data - Sachintha Dilhani; Suraj Perera; Nirma Alpitiarachchi; Mekala Fernando (Journal of the College of Community Physicians, 2022)
Introduction: There is a dearth of information available on baseline data on the pattern of childhood cancers in Sri Lanka.